Road Transportation Safety Through Community Empowerment - Joko Siswanto; Suprapto Hadi; Ramadhan Dwi Pasetyo; Bagus Ikapraja (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Some communities have limited access to road transport safety education programs. Not all communities are actively involved in efforts to empower road transportation safety and have the perception that the risk of accidents is something that cannot be avoided. Community empowerment regarding road transportation safety includes 4 stages (preparation, provision of pre-test, community empowerment phase, and provision of pre-test) with community results on road transportation safety. 60 people from PAUD Teachers and Transportation Service Employees were participants for 2 days with 7 topics. The majority of participants consisted of teachers (83.3%), women (90%), bachelor's degrees (60%), and over 46 years of age (51.5%). Pre-test 7 topics still below 30%. The first day's activities were phase 1 to phase 4 and the second day was phase 5 to phase 7. Post-test 7 topics were above 75%. 7 topics have increased above 50%. The improvements that occur can be the beginning of realizing road transportation safety for society.